The Relationship of Academic Achievement with Graduation of Nurse Preference Competency Test at STIKes Panrita Husada Bulukumba - Safruddin; Muriyati; Jasrullah (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2018)
National competency test is one of the effective ways to improve the educational process and management of achieving competency relevance in accordance with the competency standards required by the community. Data obtained at the Panrita Husada College of Health Sciences Bulukumba Nurse Profession in taking the 2014 Competency Test average GPA of 3.94 with a competency test reaching 62.9%, then in 2015 an average GPA of 3.73 with a competency test graduation 48.6% and in 2016 with an average GPA of 3.75 passing the competency test is decreasing at 35.7%. And it can be concluded that from year to year the passing of competency tests has decreased. The purpose of this study was to determine the relationship between academic achievement and the graduation of the Nursing Professional Competency test for Stikes Panrita Husada Bulukumba. This study uses a cross-sectional design. The sample of this study was 155 respondents with a population of 155 professional students of Stikes Panrita Husada Bulukumba. The analysis used was univariate and bivariate analysis using statistical tests of alternative unpaired T-test Mann Whitney with a significance level (α = 0.05). The results showed that based on the results of statistical analysis using the Mann Whitney test, the value of p = 0.001 <α = 0.05 based on the final results can be concluded that there is a relationship between academic achievement with the passing of the Competency Test for Nurses Stikes Panrita Husada Bulukumba. The conclusion in this study is the academic achievement of competent Ners Stikes Panrita Husada Bulukumba students has a higher number than those who are not competent. More competency tests passed and those that did not. There is a difference in the proportion between academic achievement who passed the Ners Stikes Panrita Husada Bulukumba professional competency test.